Free‐breathing multitasking multi‐echo MRI for whole‐liver water‐specific T1, proton density fat fraction, and R2∗ quantification - Wang, Nan; Cao, Tianle; Han, Fei; Xie, Yibin; Zhong, Xiaodong; Ma, Sen; Kwan, Alan; Fan, Zhaoyang; Han, Hui; Bi, Xiaoming; Noureddin, Mazen; Deshpande, Vibhas; et al. (Magnetic resonance in medicine, 2022)
Purpose To develop a 3D multitasking multi‐echo (MT‐ME) technique for the comprehensive characterization of liver tissues with 5‐min free‐breathing acquisition; whole‐liver coverage; a spatial resolution of 1.5 × 1.5 × 6 mm3; and simultaneous quantification of T1, water‐specific T1 (T1w), proton density fat fraction (PDFF), and R2∗. Methods Six‐echo bipolar spoiled gradient echo readouts following inversion recovery preparation was performed to generate T1, water/fat, and R2∗ contrast. MR multitasking was used to reconstruct the MT‐ME images with 3 spatial dimensions: 1 T1 recovery dimension, 1 multi‐echo dimension, and 1 respiratory dimension. A basis function–based approach was developed for T1w quantification, followed by the estimation of R2∗ and T1‐corrected PDFF. The intrasession repeatability and agreement against references of MT‐ME measurements were tested on a phantom and 15 clinically healthy subjects. In addition, 4 patients with confirmed liver diseases were recruited, and the agreement between MT‐ME measurements and references was assessed. Results MT‐ME produced high‐quality, coregistered T1, T1w, PDFF, and R2∗ maps with good intrasession repeatability and substantial agreement with references on phantom and human studies. The intra‐class coefficients of T1, T1w, PDFF, and R2∗ from the repeat MT‐ME measurements on clinically healthy subjects were 0.989, 0.990, 0.999, and 0.988, respectively. The intra‐class coefficients of T1, PDFF, and R2∗ between the MT‐ME and reference measurements were 0.924, 0.987, and 0.975 in healthy subjects and 0.980, 0.999, and 0.998 in patients. The T1w was independent to PDFF (R = −0.029, P = .904). Conclusion The proposed MT‐ME technique quantifies T1, T1w, PDFF, and R2∗ simultaneously and is clinically promising for the comprehensive characterization of liver tissue properties.